Weapons of Mass Destruction (WMD) An Overview - Albedwawi, Salim Ali Abdulla Mohamed (South Asian Journal of Social Sciences and Humanities, 2022)
The international community witnessed a significant development in the field of non-conventional weapons. Nations sought to invent weapons of immense destructive power. This paved the way for an arms race among the supremacy nations. By using doctrinal legal research methodology, this article aims to examine weapons of mass destruction (hereinafter referred to as “WMDs”). For this reason, this article identifies the concepts of WMDs, the nature of WMDs, and the legal perspective of the International Court of Justice (hereinafter referred to as “ICJ”) on the threat or use of WMDs. Primary and secondary data are critically and analytically examined using content analysis method. It is discovered that regardless of the efforts made by the international community to disarm WMDs and avoid their dangers, WMDs suffer from the problem of the domination of superpowers. This article introduced several recommendations to achieve the objectives of the ICJ in providing a safe environment and avoiding the catastrophic impact of using WMDs on the environment.